Familial pseudohyperkalemia induces significantly higher levels of extracellular potassium in early storage of red cell concentrates without affecting other standard measures of quality: A case control and allele frequency study. Issue 8 (7th May 2021) - Meli, Athinoula; McAndrew, Margaret; Frary, Amy; Rehnstrom, Karola; Stevens‐Hernandez, Christian J.; Flatt, Joanna F.; Griffiths, Alexandra; Stefanucci, Luca; Astle, William; Anand, Rekha; New, Helen V.; Bruce, Lesley J.; et al.
Abstract: Background: Familial pseudohyperkalemia (FP) is characterized by an increased rate of potassium leakage in refrigerated red cells and is associated with the minor allele of the single nucleotide polymorphism rs148211042 (R723Q) in the ABCB6 gene. The study aims were to obtain the minor allele frequencies of ABCB6 variants and to measure supernatant potassium accumulation, and other red cell storage parameters, in red cell concentrates (RCC) from carriers of variant rs148211042 under standard blood bank conditions. Study Design: Whole blood units were collected from 6 FP individuals and 11 controls and processed into RCC in additive solution. RCC were sampled and tested over cold storage for full blood count, extracellular potassium, glucose, lactate, microvesicle release, deformability, hemolysis, pH, adenosine triphosphate, and 2, 3‐diphosphoglycerate. Results: Screening of genotyped cohorts identified that variant rs148211042 is present in 1 in 394 British citizens of European ancestry. FP RCC had significantly higher supernatant potassium at all time points from day 3 onwards ( p  < .001) and higher mean cell volume ( p  = .032) than controls. The initial rate of potassium release was higher in FP RCC; supernatant potassium reached 46.0 (23.8–57.6) mmol/L (mean [range]) by day 5, increasing to 68.9 (58.8–73.7) mmol/L by day 35. Other quality parameters were not significantly different between FP RCC and controls. Conclusion: These data suggest that if a blood donor has FP, reducing the RCC shelf‐life to 5 days may be insufficient to reduce the risk of hyperkalemia in clinical scenarios such as neonatal large volume transfusion.